2019
DOI: 10.1177/1526602819836749
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Atherectomy Plus Drug-Coated Balloon Angioplasty for the Treatment of Total In-Stent Occlusions in Iliac and Infrainguinal Arteries

Abstract: Purpose: To analyze the long-term outcomes of a hybrid treatment method combining rotational atherectomy with drug-coated balloon (DCB) angioplasty in patients with total in-stent occlusion in the iliac and/or infrainguinal arteries. Materials and Methods: Between April 2014 and June 2017, 74 consecutive patients (mean age 66.7±9.7 years; 49 men) with total occlusion of a previously implanted stent underwent endovascular recanalization using the Rotarex system and DCB angioplasty. Half (37, 50%) of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…However, our bail‐out stenting rates were still higher compared to rates reported by RCTs of DCBs for FP ISR . This can be explained by their shorter average lesion length and lower rate of Tosaka III lesions . Most of the studies that examined DCBs with or without LA for the treatment of FP‐ISR are also limited to 1‐year outcomes.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, our bail‐out stenting rates were still higher compared to rates reported by RCTs of DCBs for FP ISR . This can be explained by their shorter average lesion length and lower rate of Tosaka III lesions . Most of the studies that examined DCBs with or without LA for the treatment of FP‐ISR are also limited to 1‐year outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“…The study compared DCB versus BA only and found a superiority for the DCB arm which started as early as at 6‐month follow‐up (Freedom from TLR rates: 100% vs. 79%; p = .004) and persisted up to 2‐years (81% vs. 50%, p = .007). Similar to the DEBATE ISR study, ISAR‐PEBIS included shorted lesions (average 140 mm), with almost 30% Tosaka I lesions, while the percentage of Tosaka III in the whole population was less than 35% (vs. 70% in our study) and the studied population consisted almost entirely of claudicants (only one CLI patient in each arm) …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Main data regarding the utility of MATH using the Rotarex S device in the management of acute and subacute lower limb occlusive disease and its potential contribution in prolonging the durability of endovascular revascularization are coming mainly from retrospective studies ( Table 1) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Looking at the literature, we identified 16 clinical studies, which evaluated MATH using the Rotarex S device as a primary treatment during revascularization interventions in patients with peripheral arterial occlusive disease in iliac, femoral, and/or popliteal arteries.…”
Section: Current Role Of "Math" Using Rotarex S Device In Peripheral mentioning
confidence: 99%
“…Three retrospective studies assessed the use of Rotarex S MATH with or without adjunctive therapy (e.g., PTA, DCB, stenting) in the treatment of femoro-popliteal in-stent restenosis or occlusion in a population of 234 patients and showed very encouraging technical success rates ranging from 96.9 to 98.6% (6,20,21).…”
Section: Rotarex S "Math" For In-stent Restenosis/occlusionmentioning
confidence: 99%